Planning and Budgeting of Medical Devices Among Ethiopian Public Hospitals - Gamessa TW; Abebe ST; Abate LD; Abo MK; Mekonnen AA; Tadesse ZK; Woyesa AF; Obse RB; Ibrahim MA; Simegn GL (Dove Medical Press, 2022)
Tadesse Waktola Gamessa,1 Samuel Tadesse Abebe,1 Lemlem Degafu Abate,1 Megersa Kebede Abo,1 Alemu Abibi Mekonnen,1 Zerihun Ketema Tadesse,1 Addisu Fayera Woyesa,1 Regasa Bayisa Obse,1 Mahdi Abdella Ibrahim,1 Gizeaddis Lamesgin Simegn2 1Pharmaceticals and Medical Equipment Directorate, Ministry of Health, Addis Ababa, Ethiopia; 2School of Biomedical Engineering, Jimma Institute of Technology, Jimma University, Jimma, EthiopiaCorrespondence: Tadesse Waktola Gamessa, Pharmaceuticals and Medical Equipment Directorate, Ministry of Health, Addis Ababa, Ethiopia, Tel +251910201915, Email tadessewatola@gmail.comBackground: Planning and budgeting of medical devices allow a healthcare institution to properly use funds, acquire quality and efficient medical devices, and improve healthcare service delivery. The lack of proper policy in the procurement and management of medical devices causes inappropriate usage of funds and impedes the quality of a product. This study aimed to identify the current practices and gaps in the planning and budgeting of medical devices in Ethiopian public hospitals. In this study, an assessment was conducted in all regional public hospitals to assess the current status of medical device management, identify the gaps, and provide suggestions for areas of improvement.Methods: A descriptive cross-sectional design was used for the study assessment where a structured data collection tool was utilized to collect data. A multi-stage stratified random sampling proportionate to size technique was employed for the sampling of public hospitals in all regions of Ethiopia. The collected data was analyzed using SPSS version 26 software.Results: The availability of medical equipment development plans, budgeting, and spare parts procurement plans were found to be below 50% in public hospitals. It was also noted that 40.3% of hospitals do not prepare medical device technical specifications during procurement orders. Moreover, the engagement of biomedical engineers/technicians in the planning and procurement of medical devices was found to be below 50%.Conclusion: This assessment showed that there is a need for improvement in the development of procurement plans and preparation of technical specifications for medical devices in Ethiopian public hospitals. Developing policies and strategies for the proper use of funds in the procurement of medical devices, involving biomedical engineering professionals in the planning, procurement and use of medical devices could help to improve the quality, optimized utilization and efficiency of medical devices and ultimately enhance healthcare service delivery.Keywords: biomedical engineering professionals, budgeting, medical device, planning, public hospitals